2013
DOI: 10.1182/blood.v122.21.5109.5109
|View full text |Cite
|
Sign up to set email alerts
|

Brentuximab Vedotin: A Promising Therapeutic Option In An HIV Patient With Advanced Hodgkin lymphoma and Significant Hyperbilirubinemia From Liver Involvement

Abstract: Case report A 54-year-old male with AIDS based on a CD4 count of 48, and viral load of 71653 IU/ml was admitted to our institution for evaluation of ongoing fevers, chills, night sweats, and pancytopenia. His evaluation included a bone marrow aspiration and biopsy which showed diffuse infiltration by classical Hodgkin lymphoma. He had rapidly progressive cholestatic liver abnormalities with a bilirubin that peaked at 27.8 mg/dl. He underwent a liver biopsy which also showed involvement by cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…But when the bilirubin levels failed to improve, brentuximab vedotin 1.4 mg/m 2 was given which rapidly normalized the bilirubin levels and improved the clinical condition of the patient. 9 Brentuximab vedotin is a monoclonal antibody directed against cells with CD30. A study on brentuximab vedotin showed that it can be used as a bridging therapy to improve hepatic function.…”
Section: Discussionmentioning
confidence: 99%
“…But when the bilirubin levels failed to improve, brentuximab vedotin 1.4 mg/m 2 was given which rapidly normalized the bilirubin levels and improved the clinical condition of the patient. 9 Brentuximab vedotin is a monoclonal antibody directed against cells with CD30. A study on brentuximab vedotin showed that it can be used as a bridging therapy to improve hepatic function.…”
Section: Discussionmentioning
confidence: 99%